PENGARUH PEMBIAYAAN MUDHARABAH,MUSYARAKAH, MURABAHAH, ISTISHNA DAN IJARAH TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH DI INDONESIA - Deasy Rahmi Puteri; Inten Meutia; Emylia Yuniartie (AKUNTABILITAS, 2014)
This research aimed at knowing the effect of mudaraba, musyaraka, murabaha, istishna, and ijarah financing on the profitability of Sharia Commercial Banks in Indonesia.  The profitability is measured by using return on assets (ROA).  The data used in this research were collected from the Quartely Financial Report Published by Sharia Commercial Banks during period of 2009-2013.  The sampling method of this research  is using purposive sampling.  The samples consist of three Sharia Commercial Banks.  Those are Bank Muamalat Indonesia, Bank Mandiri Syariah, and BRI Syariah.  The technical analysis used in reasearch is multiple linear regression.  This research found that the mudharabah and musyaraka financing have negative effect, while murabahah, istishna,and ijarah have positive effect on profitability of Sharia Commercial Banks in Indonesia.  However, only murabaha and istishna have significant effect on profitability of Sharia Commercial Banks in Indonesia.